KEMAMPUAN MENULIS KREATIF PUISI MENGUNAKAN PENDEKATAN KONTEKSTUAL SMP KRISTEN KANAAN SEI RAYA DALAM - Kingdo, Firminus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research problem is how do planning, process and learning creative writing poetry using a contextual approach. The purpose of this study is to analyze and assess the application of contextual approach can improve the ability of creative writing poems in class VII student of Christian Canaan Junior High School Sei Raya Dalam. This research method using descriptive method qualitative forms of research data source of this research is the Indonesian teacher and students. Beginning in the first cycle test showed that of 9 students, categorized pass the study amounted to 7 people or 77.7 %. In the second cycle from 9 students who take the learning process. Student who pass the study categorized amounted to 9 or 100 %. Increased skill learning creative writing poetry uses contextual approach significantly seen in the increase in the average grade is 6. Best on the result of research and discussion of classroom action research, it can be concluded that the application of contextual approach can increase the result of test of creative writing student poetry.Keywords: Creative Writing, Contextual ApproachÂ